Sponges to Be Winners under Near-Future Climate Scenarios. (4th December 2018) - Bell, James J; Bennett, Holly M; Rovellini, Alberto; Webster, Nicole S
Abstract: Sponges are functionally important components of global benthic environments and have been proposed as potential winners under future climate scenarios. We review the evidence to support this hypothesis by examining the individual and combined effects of ocean warming (OW) and ocean acidification (OA) on sponges and comparing sponge responses with tolerance thresholds for other benthic organisms. Although sponges are generally tolerant of OA and may even benefit from elevated partial pressure of carbon dioxide, they are often sensitive to seawater temperatures only a few degrees higher than their normal range. Sponge responses to the combined effects of OA and OW are generally more positive than their response to OW alone. We found that sponges are generally less affected by OW or OA than are a number of currently dominant benthic organisms, such as corals. Therefore, sponges are expected to benefit under near-future climate scenarios, although species-specific differences in tolerance will likely shift the sponge assemblage composition toward more resilient species.